Motivating Students in L2 Reading through Dialogue Journal: An Investigation on Students’ Perception - Paradita, Lanoke Intan (Universitas Muhammadiyah Yogyakarta, 2018)
Reading is one of the sources of input that plays a crucial role in foreign language learning, yet low reading motivation remains a challenge. While the premise to motivate reading is by reading itself, EFL students would require more attention. This study is to investigate students’ perspective on their practice of writing dialogue journal, which is intended as a tool for a teacher to develop students’ motivation in reading. Five interviews with freshman were analyzed to find out what aspects they perceived to be facilitated by the written commentary in the dialogue journal. The analysis revealed that both students’ cognitive and affective aspects were mostly reinforced, thus supporting the development of reading motivation.